Polimorfismos nos genes IL1B e IL1RN em pacientes com osteomielite - Souza, Clinio Alves de (2013)
Osteomyelitis is a debilitating disease of the bone and it is associated with significant morbidity and mortality. It is usually due to infection and characterized by severe inflammation and progressive bone destruction. Infection can occur as a result of hematogenous spread or from a contiguous source secondary to an open injury to bone caused by trauma, bone surgery or joint replacement. Staphylococcus aureus is the most commonly isolated pathogen in any type of osteomyelitis. A combination of medical and surgical approaches should be considered for all cases of osteomyelitis, but sometimes, this treatment is unsuccessful. New approaches are necessary. There is evidence that susceptibility to inflammation is influenced by genetic variation in cytokine genes. The proteins IL-1α, IL-1β and IL-1Ra are potent mediators of the inflammatory response, therefore genes encoding these cytokines are important candidates which may be implicated in pathogenesis of osteomyelitis. A polymorphic site in intron 2 of the IL1RN gene consisting in a variable number tandem repeats (VNTR, 86 pb repeats) has been extensively investigated in relation to a variety of pathological conditions. Increased frequency of the allele IL1RN*2 has been associated with more severe clinical outcome in several chronic inflammatory diseases. Therefore, in the present study it was investigated the association of IL1RN and IL1B polymorphisms and osteomyelitis in patients with bone fractures in a Northeaster Brazilian population. One hundred one patients attended in the emergency of Instituto Dr. José Frota (IJF), a trauma hospital, were randomly selected. The IL1RN (VNTR) polymorphism was determined by polyacrylamide gel electrophoresis after PCR amplification. Twenty-seven patients developed osteomyelitis. The infection was more frequent in patients with open fractures in long bones. The allele IL1RN*2 was significantly associated with the increased risk of osteomyelitis in Northeastern Brazilians (p=0.003), (p-value considered significant at p<0.05, statistical softwares: SPSS ver. 13.0 and Epi Info 7.0). The present study showed promising results for the use of IL1RN (VNTR) polymorphism as a biomarker in treatment and follow up of patients with open fractures.